Effects of fishing on a temperate reef community in South Africa 1: ichthyofauna - Götz, A; Kerwath, S E; Attwood, C G; Sauer, W HH (African journal of marine science, 2009)
Exploitation of temperate reef fish not only affects the target species but potentially changes the composition of reef fish assemblages. This study investigated the effect of fishing on the ichthyofaunal community at protected and exploited sites around the Goukamma Marine Protected Area (MPA) on the South African temperate south coast. Abundance and size frequency data from 273 standardised angling and 44 underwater visual census sites were analysed with generalised linear modelling and multivariate techniques to separate the effects of exploitation, habitat, time of day and season. Ichthyofaunal communities differed significantly between protected and exploited sites, which is likely a result of differential fishing pressure. Abundance and size of roman Chrysoblephus laticeps, the dominant species of the local linefishery, were significantly lower at exploited sites. Non-target species with considerable dietary overlap with roman were significantly less abundant inside the MPA, probably due to interspecific competition, whereas species whose diets differed to that of roman were more abundant at protected sites. The results show that fishing can have an influence on the composition of target and non-target species and that these effects need to be considered in fisheries management and conservation planning.